The role of immune mechanisms in kidney damage in hemorrhagic fever with renal syndrome - M. F. Ivanov; D. Yu. Konstantinov; I. P. Balmasova; A. Yu. Ulitina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The study is devoted to the assessment of the role of immune mechanisms in the development of acute renal failure in HFRS. The material for the study was the blood of 65 patients with HFRS and 17 patients with ALF of toxic nature from the comparison group as models of kidney damage by hantavirus and non-infectious genesis and 15 clinically healthy subjects of the control group. Data were obtained that allow us to consider the cytolytic effects of natural killer cells and cytotoxic T-lymphocytes activated by the NKG2D-dependent method as damage factors, including renal tissue, and a significant increase in the content of regulatory T-cells in the blood as protective mechanisms.